Head circumference growth curves in children 0 to 3 years of age. a new approach - González-Bejarano, Laila Yaned; Tejedor, Fabio Hernán; López-Pérez, Luis Alberto; Infante-Contreras, Clementina (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: head circumference is an indicator of health and global cranial growth in early childhood, so it must be monitored. Usually, the WHO reference patterns use the Box Cox Power exponential model and the LMS method to model the behavior of head circumference growth. These methods are limited because they compare each individual against the median of a population, which prevents characterizing individual growth, while mixed-effect longitudinal models allow assessing individual growth patterns and controlling variability among subjects. The objective of this study was to use mixed-effect longitudinal models to characterize growth patterns based on head circumference in children 0 to 3 years of age. Methods: being a prospective longitudinal study, the criteria for children eligibility considered inclusion and exclusion factors (WHO); 265 Colombian children (116 girls, 149 boys) living in Bogotá were distributed in 3 groups: G1: (0-12], G2: (12-24], G3: (24-36] months. They were measured every 3 months for 1 year. Two examiners were trained and continuously standardized, and they were monitored on adherence to data quality and data collection procedures. Random and systematic errors were calculated. Growth curves were constructed using mixed longitudinal models. The model was estimated through the method of estimation of restricted maximum likelihood (REML), free R statistical software, version 2.15. To adjust the models, we used the lme4 package. Results: 6 models were adjusted, with maximum gradient of growth from 0 to 12 months. The model showed a growth pattern by age group and sex, in groups G1 and G2, confidence bands allowed identifying atypical data, better adjustment, and distribution of residuals, contrary to the behavior in group G3, which showed more atypical data outside the bands. Conclusions: this methodology allowed understanding the behavior of head circumference by age group and sex, and analyzing data with unbalanced structures.